2022
DOI: 10.1037/hea0001131
|View full text |Cite
|
Sign up to set email alerts
|

Social support and HIV prevention behaviors among urban HIV-negative gay, bisexual, and other men who have sex with men.

Abstract: Objective: Supportive social relationships can have direct positive effects on health and mitigate the negative impact of stressors. This study investigated the main effect of perceived social support on STI/HIV risk and prevention behaviors. The buffering effect of perceived social support on the impact of proximal minority stressors, like internalized homonegativity, was also examined on one risk behavior specifically, condomless anal sex (CAS) without HIV pre-exposure prophylaxis (PrEP) use. Methods: HIV-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Sexual minority populations are at elevated risk for loneliness due to experiences of exclusion and stigmatization from family and peers (Gorczynski & Fasoli, 2022; Meyer, 2003; Mongelli et al., 2019; Tan & Saw, 2022)—a problem that was only exacerbated during the COVID‐19 pandemic. Because strict measures were implemented to stem the spread of COVID‐19, sexual minority individuals may have lost access to crucial support systems that mitigate the adverse effects of loneliness (Al‐Khouja et al., 2021; Hart et al., 2017; Hsieh, 2014; Skakoon‐Sparling et al., 2021; Wang et al., 2018; Xu et al., 2020). Loss of these support systems and subsequent feelings of loneliness may have unintended consequences in terms of risk‐taking behaviors for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual minority populations are at elevated risk for loneliness due to experiences of exclusion and stigmatization from family and peers (Gorczynski & Fasoli, 2022; Meyer, 2003; Mongelli et al., 2019; Tan & Saw, 2022)—a problem that was only exacerbated during the COVID‐19 pandemic. Because strict measures were implemented to stem the spread of COVID‐19, sexual minority individuals may have lost access to crucial support systems that mitigate the adverse effects of loneliness (Al‐Khouja et al., 2021; Hart et al., 2017; Hsieh, 2014; Skakoon‐Sparling et al., 2021; Wang et al., 2018; Xu et al., 2020). Loss of these support systems and subsequent feelings of loneliness may have unintended consequences in terms of risk‐taking behaviors for this population.…”
Section: Introductionmentioning
confidence: 99%
“…In the minority stress model, access to social support is an important coping mechanism for dealing with minority stress 15. Belonging to a community can lessen the psychological aspect of stress process, most especially for single MSM 30 31. Research has shown that in the absence of group-level resources, even the most resourceful individuals have been found to struggle to cope 7.…”
Section: Discussionmentioning
confidence: 99%
“…Social capital has also been associated with men's sexual and reproductive health. Studies have found that high social capital levels decreased men's risk for acquiring STIs [ 33 ] and facilitated HIV testing among men who have sex with men (MSM) [ 34 ]. However, contradictory results have also been reported.…”
Section: Introductionmentioning
confidence: 99%